Corporate Governance and firm’s performance: evidence from Euronext Lisbon - Nogueira, João Carlos da Silva (2023)
This dissertation aims to examine de relationship between several Corporate Governance (CG) characteristics and performance in Portuguese listed companies. This study is based on a sample of Portuguese listed firms for a period between the years of 2010 to 2020. The main results show that higher level of managerial ownership and gender diversity may drive to a higher level of performance. However, no evidence was found that a representation of three or more female directors leads to an increase in performance. Additionally, the results suggest there is a negative relationship between leverage and performance when this is analysed with a market-based performance measure. Finally, we found evidence that the COVID-19 pandemic had a negative impact on corporate performance.